(untitled) - Gilmore, Charles M. (Mason, OH, 2015)
Focuses on mechanical properties of materials. In addition to the introductory chapters on materials science, this title includes chapters on mechanical properties, how to make strong solids, mechanical properties of engineering materials, the effects of temperature and time on mechanical properties, and more
Keywords: Khoa học vật liệu,Materials science